Recent progress and perspectives on physiological and molecular mechanisms underlying cold tolerance of tea plants - Wang, Yanli; Samarina, Lidia; Mallano, Ali Inayat; Tong, Wei; Xia, Enhua (Frontiers in Plant Science, 2023)
Tea is one of the most consumed and widely planted beverage plant worldwide, which contains many important economic, healthy, and cultural values. Low temperature inflicts serious damage to tea yields and quality. To cope with cold stress, tea plants have evolved a cascade of physiological and molecular mechanisms to rescue the metabolic disorders in plant cells caused by the cold stress; this includes physiological, biochemical changes and molecular regulation of genes and associated pathways. Understanding the physiological and molecular mechanisms underlying how tea plants perceive and respond to cold stress is of great significance to breed new varieties with improved quality and stress resistance. In this review, we summarized the putative cold signal sensors and molecular regulation of the CBF cascade pathway in cold acclimation. We also broadly reviewed the functions and potential regulation networks of 128 cold-responsive gene families of tea plants reported in the literature, including those particularly regulated by light, phytohormone, and glycometabolism. We discussed exogenous treatments, including ABA, MeJA, melatonin, GABA, spermidine and airborne nerolidol that have been reported as effective ways to improve cold resistance in tea plants. We also present perspectives and possible challenges for functional genomic studies on cold tolerance of tea plants in the future.